Studi Literatur Pengaruh Psikologi Pendidikan terhadap Keberhasilan Pembelajaran - Nurul Rochaini (Program Studi Pendidikan IPA FKIP Universitas Jember, 2019)
Psychology is the science that talks about human behavior in the teaching and learning process, and it has a close relationship with teaching science. In the teaching and learning process, students are told to be able to understand and master all material taught by educators. Each student has different abilities. But the success of a learning is influenced by the psychological conditions (psychology) of their students. The purpose of this study was to find solutions to learning problems caused by the psychological conditions of students. If a student is in an uncomfortable, depressed, or fearful condition then any good learning method will not work.